Altered sense of agency in schizophrenia: the aberrant effect of cardiac interoceptive signals - Koreki, Akihiro; Terasawa, Yuri; Nuruki, Atsuo; Oi, Hiroki; Critchley, Hugo; Yogarajah, Mahinda; Onaya, Mitsumoto (Frontiers in Psychiatry, 2024)
Background Schizophrenia (SZ) is characterized by abnormalities in self-representation, including a disturbed sense of agency (SoA). The continuous processing of sensory information concerning the internal state of the body (interoception) is argued to be fundamental to neural representations of the self. We, therefore, tested if aberrant interoception underpins disturbances in SoA in SZ, focusing on cardiac interoceptive signaling. Methods Forty-two SZ and 29 non-clinical participants (healthy controls; HC) performed an intentional binding task to measure SoA during concurrent heartbeat recording. The effect of cardiac interoceptive signals on SoA was measured by the difference in intentional binding effect during systole and diastole. This measure was standardized based on the overall intentional binding effect to control for non-cardiac factors, and then compared between SZ and HC. Results Our study revealed a significant difference between SZ and HC groups, with opposite effects of cardiac systole on SoA. Specifically, cardiac systole disrupted SoA in SZ, contrasting with the enhanced SoA in HC. Across the SZ group, the extent to which SoA was disrupted by cardiac systole correlated significantly with a clinical proxy for symptom instability, namely the number of hospital admissions for hallucinations and delusions. Furthermore, the disruption was particularly observed in patients with severe hallucinations. Conclusions This study revealed a disturbance in the impact of cardiac interoceptive signals on an implicit index of SoA in schizophrenia. This supports the notion that pathophysiological disruption of the central integration of interoceptive information increases vulnerability to disturbances in self-representation and the associated expression of schizophrenic symptoms.